Effects of Body Condition on Facultative Anadromy in Brown Trout (Salmo trutta) - Shry, Samuel (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2018)
Fish behavior and life history is influenced by factors such as the environment, genetics, and their physiological state. One key life history stage in brown trout is decision to migrate to the sea or reside in the river. The energy status and body condition of the fish is thought to play a role in the timing and duration of migration to the sea. In this study, I examined the role of body condition in the initiation of this life history stage and determined the importance of feeding regimes in the physiological trade-off between migration and residency. I used four different feeding regimes in age one and age two cohorts of hatchery-reared brown trout to observe if starvation or feeding saturation induce behavioral changes in migration both in a controlled environment as well as a natural river system. I used both passive integrative transponder tags (PIT) as well as acoustic telemetry tags to analyze migration. I was successfully able to manipulate body condition using variable feeding regimes in both cohorts and I found that migration initiation and behavior was influenced by feeding regime. Feeding increased migration in both cohorts in the laboratory setting, but not in the natural setting. Laboratory migration in the age two cohort was primarily independent of feeding treatments as almost all age two fish migrated, but migration intensity was found to be greater with fed treatment groups. In contrast, age one fish were highly influenced by feeding regime, with fewer starved fish migrating and at a slower rate. Downstream migration in the wild was extremely low for both cohorts independent of feeding treatment. Overall, the findings indicate that age at release and feeding condition prior to release can impact migration initiation and duration. The results contribute to a better understanding of this complex life history stage and the mechanisms involved in the initiation, behavior, and survival of migrating brown trout.